Regulation of Aryl Hydrocarbon Receptor Function by Selective Estrogen Receptor Modulators - DuSell, Carolyn D. (The Endocrine Society, 2010)
Selective estrogen receptor modulators (SERMs), such as tamoxifen (TAM), have been used extensively for the treatment and prevention of breast cancer and other pathologies associated with aberrant estrogen receptor (ER) signaling. These compounds exhibit cell-selective agonist/antagonist activities as a consequence of their ability to induce different conformational changes in ER, thereby enabling it to recruit functionally distinct transcriptional coregulators. However, the observation that SERMs can also regulate aspects of calcium signaling and apoptosis in an ER-independent manner in some systems suggests that some of the activity of drugs within this class may also arise as a consequence of their ability to interact with targets other than ER. In this study, we demonstrate that 4-hydroxy-TAM (4OHT), an active metabolite of TAM, directly binds to and modulates the transcriptional activity of the aryl hydrocarbon receptor (AHR). Of specific interest was the observation, that in the absence of ER, 4OHT can induce the expression of AHR target genes involved in estradiol metabolism, cellular proliferation, and metastasis in cellular models of breast cancer. The potential role for AHR in SERM pharmacology was further underscored by the ability of 4OHT to suppress osteoclast differentiation in vitro in part through AHR. Cumulatively, these findings provide evidence that it is necessary to reevaluate the relative roles of ER and AHR in manifesting the pharmacological actions and therapeutic efficacy of TAM and other SERMs.